EXPONENTIATED DISCRETE WEIBULL DISTRIBUTION FOR CENSORED DATA - CARDIAL, Marcílio Ramos Pereira; FACHINI-GOMES, Juliana Betini; NAKANO, Eduardo Yoshio (Brazilian Journal of Biometrics, 2020)
This paper further develops the statistical inference procedure of the exponentiated discrete Weibull distribution (EDW) for data with the presence of censoring. This generalization of the discrete Weibull distribution has the advantage of being suitable to model non-monotone failure rates, such as those with bathtub and unimodal distributions. Inferences about EDW distribution are presented using both frequentist and bayesian approaches. In addition, the classical Likelihood Ratio Test and a Full Bayesian Signiﬁcance Test (FBST) were performed to test the parameters of EDW distribution. The method presented is applied to simulated data and illustrated with a real dataset regarding patients diagnosed with head and neck cancer.